DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR THE QUANTITATIVE DETERMINATION OF ORGANIC IMPURITIES OF DOCETAXEL IN PARENTERAL FORMULATION OF DOCETAXEL USING UV DETECTOR - LINGA REDDY MALLAMPATI R,; JAGANMOHAN REDDY B, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective is to develop a novel, rapid, simple, precise, accurate, and reproducible reverse-phase high-performance liquid chromatography (RP-HPLC) method for quantitative estimation of organic impurities of docetaxel (DTX) parenteral formulation through high-performance liquid chromatography (HPLC). Methods: Finalized chromatographic conditions were used for a reversed-phase C18 column with particle size of 3 μm and dimension of 4.6×150 mm, water as mobile phase-A and acetonitrile mobile phase-B. The flow rate is 1.2 mL/min with gradient elution and ultraviolet (UV) detection at 232 nm. Acetonitrile: water:glacialcetic acid in the ratio of 100:100:0.1 (v/v/v) as diluent. Results: Analytical test method for the quantitative determination of organic impurities of DTX in parenteral formulation of DTX using HPLC with UV detector was verified and found to be linear over the tested concentration range for all impurities (10-deacetylbaccatin: 0.032–0.466 μg/mL; DTX: 0.015–0.151 μg/mL; 6-oxodocetaxel: 0.023–2.080 μg/mL; 4-epidocetaxel: 0.022–1.380 μg/mL; 4-epi-6-oxodocetaxel: 0.021–0.673 μg/mL). The calibration charts plotted were linear with a regression coefficient of R2>0.999. Method-precise results were found to be within the acceptance criteria. Limit of detection and limit of quantification for the active ingredients and their impurities were established with respect to test concentration. Conclusion: It was concluded that the method is simple, sensitive, precise, and accurate and hasthe ability to separate the drug from degradation products and excipients found in the dosage form.